The Effectiveness of Tax Audit in Achieving Tax Revenue at the Jakarta Kelapa Gading Primary Tax Service Office - Yani, Ahmad; Bambang, Bambang (Riviera Publishing, 2024)
The tax collection system implemented in Indonesia is the Self Assessment System. This system has a loophole in the form of taxpayers' incorrect submission of tax returns. The Directorate General of Taxes has the authority to supervise and coach the compliance of taxpayers through administrative supervision and tax audits. This study aims to measure the level of Effectiveness of the implementation of tax audits at the Jakarta Kelapa Gading Pratama Tax Service Office based on the completion of SP2 and based on the realization of receipts from tax audit activities. This study uses a type of descriptive research with a qualitative approach. As well as data collection techniques using literature studies and field studies. The results of this research show that based on the indicators of tax audit effectiveness explained by Richard M Steers (2020), namely the achievement of goals, integration, and Adaptation, it is found that the process of implementing tax audit has been running well and is in accordance with the guidelines of tax audit and existing regulations but in its implementation has not been effective, this can be seen from several obstacles during tax audits, Starting from the limited number of employees to the scope of work that is too broad. This causes the tax audit to not reach the set target. The Jakarta Kelapa Gading Primary Tax Service Office is expected to prevent and reduce existing obstacles so that the tax audit process can run more effectively and better.